Methodology of Darwazah and Its Contribution to the Interpretation of the Qur'an: Study of the Book of Al-Tafsir al-Hadith: Tartib al-Suwar Hasb al-Nuzul - Fithrotin Fithrotin; Aswadi Aswadi; Iffah Muzammil (Aloha International Journal of Multidisciplinary Advancement (AIJMU), 2021)
Darwazah thinking was a response to orientalist thought and a critical reaction to the study's previous interpretation. It gives rise to a logical method and by the demands of modern times to meet the needs of the younger generation to understand the Qur'an that was previously in the style of traditional interpretation and tends to leave it tartib al nuzul. The purpose of writing is to conduct a study of the methodology of interpretation of Darwazah in his book using various sources and contributions to the understanding of the Qur'an. The advantages of the Darwazah Method is that the arrangement is based on tartib al nuzul, which is different from the previous mufassir, has something to do with the systematic understanding between darwazah's earlier works the combination of the Qur'an with history, and following prophetic history and the chronology of revelation from time to time. This research uses a qualitative approach with method library research. This type of research is descriptive analysis with data collection techniques in documentation studies using content analysis techniques. The primary source is al-Tafsir al-Hadith's.The results showed that the basis of the interpretation of the Qur'an, Hadith, reason, social context of society, previous performances, 'ulum Qur'an, and history. The method of interpretation is nuzuli-tajzi'i-tahlili and its tendency to account and socio-politics. The basic assumption that the Qur'an is a living nas and most of its verses are a response to the events of its descent gradually derived following the history in Makkah and Medina according to the Qur'an nuzuli. Contribution to the Interpretation of the Qur'an is to contribute to determine the chronological order of the steps of mawdu'i interpretation and facilitate the application of interpretation steps with thematic and contextual approaches that pay attention to the socio-historical context. Keywords: Tartib al Nuzul; contributions; interpretation